Identifikasi nilai sikap masyarakat terhadap pengembangan potensi budidaya kepiting bakau (Scylla serrata) di desa Sumberwaru kecamatan Banyuputih kabupaten Situbondo - Sasanti Sihsubekti; Dayang Diah Fidhiani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
This study aims to identify the value of community attitudes towards the potential of mangrove crab (Scylla serrate) cultivation in Sumberwaru Village, Banyuputih District, Situbondo Regency. The research location was determined purposively (intentionally) in the coastal and coastal areas of Sumberwaru Village, Banyuputih District, Situbondo Regency. Determination of respondents using purposive sampling technique and the number of respondents as many as 55 people. The results showed that the stages of the attitude of the Sumberwaru Village community at the affective, cognitive, and conative stages, which means that from the field conditions, it is known that the value of the Sumberwaru Village community's attitude towards the development of the potential for mangrove crab cultivation is still in the growing stage and requires continuous assistance by more competent parties. so that the national development goals of local potential-based regional development (mangrove crab cultivation) can be achieved optimally.